Antimicrobial peptide Pc-pis: A new cancer cell killer. Issue 81 (October 2018) - Zhou, Hua-Min; Li, Da-Cheng; Wang, Yi-Ying; Zhu, Huan; Su, Yong-Quan; Mao, Yong
Abstract: The antimicrobial peptide (AMP) Pc-pis, a member of Piscidin family from ﬁsh with cationic amphipathic structure, has potent, broad-spectrum antimicrobial activity against bacteria, fungi and parasite, and lower hemolytic activity. Here, we reported that Pc-pis had antitumor activity. Pc-pis killed tumor cells including HeLa cells. Previously, it is reported that AMPs bind to the membrane of bacteria to generate the pores to lyse the target cells, and similarly, the cancer cell incorporate phosphatidyl-serine on the outer leaflet of plasma membrane so that amphipathic AMPs can bind to the membrane to kill it. Our data supported that notion because suitable size osmo-protectant PEG4000 prevented HeLa cells from death induced by Pc-pis. Additionally, Fusion protein GFP-Pc-pis accumulated mainly at the nuclear membranes of HeLa cells and positive net charge in modified Pc-pis intensified but negative net charges eliminated this effect. Thus, positively charged residues were important for its affinity to the membrane. Our work will lay the groundwork of the development of Pc-pis antitumor activity. Highlights: Pc-pis killed tumor cells. Osmoprotectant PEG4000 prevented HeLa cells from death induced by Pc-pis. Positively charged residues are key for GFP-Pc-pis binding to the membrane.